2003
DOI: 10.1002/jcb.10584
|View full text |Cite
|
Sign up to set email alerts
|

Epiregulin is more potent than EGF or TGFα in promoting in vitro wound closure due to enhanced ERK/MAPK activation

Abstract: Epiregulin (EPR) is a broad specificity EGF family member that activates ErbB1 and ErbB4 homodimers and all possible heterodimeric ErbB complexes. We have previously shown that topical EPR enhances the repair of murine excisional wounds. The purpose of this study was to determine whether EPR was more effective than EGF or TGFalpha in promoting in vitro wound closure and to compare the EPR induced signal transduction pathways with those activated by EGF and TGFalpha. Normal human epidermal keratinocytes or A431… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 53 publications
7
50
0
Order By: Relevance
“…In recent years, the regulation of re-epithelialization has been shown to require three major MAPK pathways: ERKs (Draper et al 2003;Kansra et al 2004), JNK (Huang et al 2003;Reed et al 2001), and p38 MAPK (Sharma et al 2003;Stoll et al 2003). Evidence is mounting that multiple pathways of MAPKs are involved in the migration both of single cells and of monolayer cells (Altan and Fenteany 2004;Li et al 2004;Turchi et al 2002Turchi et al , 2003Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, the regulation of re-epithelialization has been shown to require three major MAPK pathways: ERKs (Draper et al 2003;Kansra et al 2004), JNK (Huang et al 2003;Reed et al 2001), and p38 MAPK (Sharma et al 2003;Stoll et al 2003). Evidence is mounting that multiple pathways of MAPKs are involved in the migration both of single cells and of monolayer cells (Altan and Fenteany 2004;Li et al 2004;Turchi et al 2002Turchi et al , 2003Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 94%
“…[33][34][35] Interestingly, the mode in which the EGF ligand is presented to KCs also appears to be important for determining whether the cells migrate or proliferate; EGF on a stationary substrate induces KC migration, while soluble EGF induces KC proliferation, suggesting that soluble and membrane-or ECM-bound EGF-family ligands play distinct roles in directing KC activities. 36 Insulin growth factor family.…”
Section: 32mentioning
confidence: 99%
“…For example, recent studies revealed that epiregulin was more potent than either epidermal growth factor or transforming growth factor-␣ in promoting both in vivo and in vitro wound closure in epidermal keratinocytes (58,59). Since the stem cell-enriched, limbal epithelial basal cell population has been shown to play a central role in wound repair, the preferential distribution of epiregulin in limbal basal cells may affect the increased proliferative response of these cells observed following wounding (4,6,28).…”
Section: Limbal and Corneal Microarray Data Are Highlymentioning
confidence: 99%